ANALYSIS OF COMPETITIVE STRATEGIES IN THE INSTITUTION OF THE XYZ SHARIA ECONOMY - Purnama, Rudi; Lukman, Syukri (JURNAL MANAJEMEN DAN BISNIS INDONESIA, 2019)
Referring to the final goal to be achieved by Islamic Economics College (STES) XYZ, from the implementation of the strategy to produce graduates who are knowledgeable, noble, and dedicated, as well as being the center of the development of science, technology and art based on Islamic values, STES XYZ is deemed necessary to work hard to improve the quality that is able to compete with other Islamic economic schools that were established first. So from that by using a qualitative approach this research was made to determine the strengths, weaknesses, and threats and opportunities of STES XYZ with the aim of obtaining the right competitive strategy that can be applied in achieving competitive advantage. The data analysis technique in this study uses 3 stages, first is the input technique with the Internal Factor Evaluating (IFE) Matrix, the External Factor Evaluating (EFE) Matrix, and the Competitive Profile matrix (CPM) matrix. Second, the matching stage in the form of a SWOT Matrix and Internal External Matrix (IE) to produce alternative strategies through the Quantitative Strategic Planning Matrix (QSPM). In addition, a balanced score card is also applied in this study to measure the quality of indicators. From the analysis obtained, STES XYZ has great potential in business development as in education. On the basis of this writing stage, researchers used the QSPM (Quantitative Strategic Planning Matrix) method to recommend a Market Development Strategy to improve school quality in competing with competing schools.